(1)∵f(x)=81n(1+ex)-9x,
∴f(x1)+f(x2)-2f()=8[1n(1+ex1)-9x1+1n(1+ex2)-9x2-21n(1+e)+9(x1+x2)]
=8[1n(1+ex1)(1+ex2)-1n(1+e)2]
=8[1n(1+ex1+ex2+ex1+x2)-1n(1+2•e+ex1+x2)].
∵x1≠x2,∴ex1+ex2>2=2•e,∴f(x1)+f(x2)-2f()>0,
∴f()<.
(2)∵f′(x)=-9=<0恒成立,∴f(x)在(-∞,+∞)上单调递减,
设A(x1,f(x1)),B(x2,f(x2)),C(x3,f(x3)),且x1<x2<x3.
∴f(x1)>f(x2)>f(x3),x2=,
∴•=(x1-x2)(x3-x2)+[f(x1)-f(x2)]•[f(x3)-f(x2)]
∵x1-x2<0,x3-x2>0,f(x1)-f(x2)>0,f(x3)-f(x2)<0,∴•<0,
故B为钝,△ABC为钝角三角形. 若△ABC是等腰三角形,则只可能是=|,
即(x1-x2)2+[f(x1)-f(x2)]2=(x3-x2)2+[f(x3)-f(x2)]2
∵x2=,∴有[f(x1)-f(x2)]2=[f(x3)-f(x2)]2,∴f(x1)-f(x2)=f(x2)-f(x3),
即:f(x2)=
即:f()=,这与(1)结论矛盾,∴△ABC不能为等腰三角形.